Growth promotion of pineapple 'vitória' by humic acids and burkholderia spp. during acclimatization Promoção do crescimento do abacaxizeiro 'vitória' por ácidos húmicos e Burkholderia spp. durante a aclimatização - Lílian Estrela Borges Baldotto (Revista Brasileira de Ciência do Solo, 2010)
In vitro propagation of pineapple produces uniform and disease-free plantlets, but requires a long period of acclimatization before transplanting to the field. Quicker adaptation to the ex vitro environment and growth acceleration of pineapple plantlets are prerequisites for the production of a greater amount of vigorous, well-rooted planting material. The combination of humic acids and endophytic bacteria could be a useful technological approach to reduce the critical period of acclimatization. The aim of this study was to evaluate the initial performance of tissue-cultured pineapple variety Vitória in response to application of humic acids isolated from vermicompost and plant growth-promoting bacteria (Burkholderia spp.) during greenhouse acclimatization. The basal leaf axils were treated with humic acids while roots were immersed in bacterial medium. Humic acids and bacteria application improved shoot growth (14 and 102 %, respectively), compared with the control; the effect of the combined treatment was most pronounced (147 %). Likewise, humic acids increased root growth by 50 %, bacteria by 81 % and the combined treatment by 105 %. Inoculation was found to significantly increase the accumulation of N (115 %), P (112 %) and K (69 %) in pineapple leaves. Pineapple growth was influenced by inoculation with Burkholderia spp., and further improved in combination with humic acids, resulting in higher shoot and root biomass as well as nutrient contents (N 132 %, P 131 %, K 80 %) than in uninoculated plantlets. The stability and increased consistency of the host plant response to bacterization in the presence of humic substances indicate a promising biotechnological tool to improve growth and adaptation of pineapple plantlets to the ex vitro environment. A propagação in vitro de abacaxizeiro produz mudas uniformes e sadias, mas exige longo período de aclimatização antes da transferência para o campo. A adaptação ao ambiente ex vitro seguida da aceleração do crescimento das mudas de abacaxizeiro é um pré-requisito para a produção de maior quantidade de material propagativo vigoroso e enraizado. A combinação de ácidos húmicos e bactérias endofíticas pode ser uma tecnologia útil para reduzir o período crítico de aclimatização. O objetivo deste trabalho foi avaliar o desempenho inicial do abacaxizeiro 'Vitória' propagado por cultura de tecidos em resposta à aplicação de ácidos húmicos isolados de vermicomposto e bactérias promotoras de crescimento de plantas (Burkholderia spp.) durante a aclimatização em casa de vegetação. Os ácidos húmicos foram aplicados nas axilas das folhas basais, enquanto as raízes foram imersas no meio bacteriano. Foram observados incrementos no crescimento da parte aérea com a aplicação de ácidos húmicos (14 %) e bactérias (102 %) quando comparado ao controle, com efeito mais pronunciado no tratamento combinado (147 %). Da mesma forma, o crescimento das raízes aumentou 50 % com ácidos húmicos, 81 % com bactérias e 105 % com o tratamento combinado. A inoculação conjunta aumentou significativamente o acúmulo de N (115 %), P (112 %) e K (69 %) nas folhas do abacaxizeiro. O crescimento do abacaxizeiro foi influenciado pela inoculação com Burkholderia spp. reforçada pela associação com ácidos húmicos, que resultou em maior massa da parte aérea e raiz e maior conteúdo de nutrientes (N, 132 %; P, 131 %; K, 80 %) quando comparado com mudas não inoculadas. A consistência da resposta da planta hospedeira para bacterização na presença de substâncias húmicas aponta para uma ferramenta biotecnológica promissora para melhorar o crescimento e a adaptação de mudas de abacaxizeiro ao ambiente ex vitro.